(untitled) (Bangladesh Journal of Child Health, 2025)
Allgrove syndrome (also known as Triple-A syndrome) is a rare disorder with autosomal recessive inheritance. About 100 cases have been described in literature. Triple-A syndrome includes ACTH resistant adrenal insufficiency, alacrima, achalasia cardia. This syndrome may affect the autonomic nervous system; in that case it is called 4A syndrome. We are reporting a case of 5-year-1-month old diagnosed as Triple–A syndrome with adrenal insufficiency and alacrima. He had alacrima since birth and developed symptoms of adrenal insufficiency since 3 years of age. We diagnosed the case on the basis of suggestive clinical features, low serum cortisol, high ACTH and whole exome sequencing. As it is a rare disease, we should query about other symptoms of Triple-A syndrome if a patient present with adrenal insufficiency. Early detection and adequate treatment can reduce morbidity and mortality. BANGLADESH J CHILD HEALTH 2023; VOL 47 (3) : 171-173